Genetic Changes of Wnt Pathway Genes Are Common Events in Metaplastic Carcinomas of the Breast - Michael Hayes; Dafydd G. Thomas; Agnieszka Emmons; Thomas J. Giordano; Celina G. Kleer (2008)
Metaplastic carcinomas are distinct invasive breast carcinomas with aberrant nonglandular differentiation, which may be spindle, squamous, or chondroid. The limited effective treatments result from the lack of knowledge of its molecular etiology. Given the role of the Wnt pathway in cell fate and in the development of breast cancer, we hypothesized that defects in this pathway may contribute to the development of metaplastic carcinomas.In 36 primary metaplastic carcinomas, we comprehensively determined the prevalence of and mechanism underlying beta-catenin and Wnt pathway deregulation using immunohistochemistry for beta-catenin expression and localization and mutational analysis for CTNNB1 (encoding beta-catenin), APC, WISP3, AXIN1, and AXIN2 genes. By immunohistochemistry, normal beta-catenin was seen as membrane staining, and it was aberrant when >5% of tumor cells had nuclear or cytoplasmic accumulation or reduced membrane staining.By immunohistochemistry, aberrant beta-catenin was present in 33 of 36 (92%) cases, revealing deregulation of the Wnt pathway. CTNNB1 missense mutations were detected in 7 of 27 (25.9%) tumors available for mutation analyses. All mutations affected the NH(2)-terminal domain of beta-catenin, presumably rendering the mutant protein resistant to degradation. Two of 27 (7.4%) tumors had mutations of APC, and 5 (18.5%) carried a frame shift mutation of WISP3. No AXIN1 or AXIN2 mutations were found.Activation of the Wnt signaling pathway is common in this specific subtype of breast carcinoma. The discovery of CTNNB1, APC, and WISP3 mutations may result in new treatments for patients with metaplastic carcinomas of the breast.